Measurement of Drag Force on different robots at varying air speeds - Mohammad Firdaus Ahmad (Universiti Malaysia Perlis, 2008)
This report presents the measurements of drag force on different robots when they are subjected to severe atmospheric conditions. It is a common experience that a body meets some resistance when it is forced to move through a fluid, especially a liquid. As an example, we feel very difficult to walk in water because of the much greater resistance it offers to motion compared to air. A fluid may exert forces and moments on a body in and about various directions. The force a flowing fluid exerts on a body in the flow direction is called drag. The drag force can be measured directly using the wind tunnel and drag balances. Drag is usually an undesirable effect, like friction, and we do our best to minimize it. Reduction of drag is closely associated with the fuel consumption in automobiles, submarines, and aircraft, improved safety and durability of structures subjected to high winds, and reduction of noise and vibration. This dissertation presents comparison of the drag force measured on three different robots mounted in three different orientations subjected to three different air speeds. This study can help us in the design of robots with less drag force for its best performance.